TRPC6 Attenuates Cortical Astrocytic Apoptosis and Inflammation in Cerebral Ischemic/Reperfusion Injury - Liu, Lu; Chen, Manli; Lin, Kun; Xiang, Xuwu; Yang, Jing; Zheng, Yueying; Xiong, Xiaoxing; Zhu, Shengmei (Frontiers in Cell and Developmental Biology, 2021)
Transient receptor potential canonical 6 (TRPC6) channel is an important non-selective cation channel with a variety of physiological roles in the central nervous system. Evidence has shown that TRPC6 is involved in the process of experimental stroke; however, the underlying mechanisms remain unclear. In the present study, the role of astrocytic TRPC6 was investigated in an oxygen–glucose deprivation cell model and middle cerebral artery occlusion (MCAO) mouse model of stroke. HYP9 (a selective TRPC6 agonist) and SKF96365 (SKF; a TRPC antagonist) were used to clarify the exact functions of TRPC6 in astrocytes after ischemic stroke. TRPC6 was significantly downregulated during ischemia/reperfusion (IR) injury in cultured astrocytes and in cortices of MCAO mice. Application of HYP9 in vivo alleviated the brain infarct lesion, astrocytes population, apoptosis, and interleukin-6 (IL-6) and IL-1β release in mouse cortices after ischemia. HYP9 dose-dependently inhibited the downregulation of TRPC6 and reduced astrocytic apoptosis, cytotoxicity and inflammatory responses in IR insult, whereas SKF aggravated the damage in vitro. In addition, modulation of TRPC6 channel diminished IR-induced Ca2+ entry in astrocytes. Furthermore, decreased Ca2+ entry due to TRPC6 contributed to reducing nuclear factor kappa light chain enhancer of activated B cells (NF-κB) nuclear translocation and phosphorylation. Overexpression of astrocytic TRPC6 also attenuated apoptosis, cytotoxicity, inflammatory responses, and NF-κB phosphorylation in modeled ischemia in astrocytes. The results of the present study indicate that the TRPC6 channel can act as a potential target to reduce both inflammatory responses and apoptosis in astrocytes during IR injury, subsequently attenuating ischemic brain damage. In addition, we provide a novel view of stroke therapy by targeting the astrocytic TRPC6 channel.